2004
DOI: 10.1128/jcm.42.12.5689-5697.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Features of Mycobacterium porcinum

Abstract: The rapidly growing mycobacterial species Mycobacterium porcinum was described in 1983 by Tsukamura et al. as a causative agent of submandibular lymphadenitis in swine (23). Tsukamura et al. characterized these strains as being similar to M. fortuitum but differing from this species by being D-mannitol and i-myo-inositol positive, nitrate negative, and succinamidase positive and utilizing benzoate as a sole source of carbon in the presence of ammoniacal nitrogen. Until recently, no isolation of this species ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 26 publications
(58 reference statements)
2
42
1
3
Order By: Relevance
“…Likewise, the modifi ed broth dilution method showed that the MIC for imipenem was <4 μg/ml for M. fortuitum (9). However, when a broth dilution method was used, the MIC for imipenem ranged from 0.5 μg/mL to 8 μg/mL in 42 M. porcinum strains (7). Together, these data challenge the susceptibility to imipenem in organisms of the M. fortuitum group.…”
Section: Mycobacterium Setense Infection In Humansmentioning
confidence: 67%
See 1 more Smart Citation
“…Likewise, the modifi ed broth dilution method showed that the MIC for imipenem was <4 μg/ml for M. fortuitum (9). However, when a broth dilution method was used, the MIC for imipenem ranged from 0.5 μg/mL to 8 μg/mL in 42 M. porcinum strains (7). Together, these data challenge the susceptibility to imipenem in organisms of the M. fortuitum group.…”
Section: Mycobacterium Setense Infection In Humansmentioning
confidence: 67%
“…We initially suspected that the water was the source of M. setense, as previously suspected for M. conceptionense (6) and reported for M. porcinum (7). However, neither M. setense nor M. setense DNA were detected in the well water in October 2007.…”
Section: Mycobacterium Setense Infection In Humansmentioning
confidence: 99%
“…In the last few years, a new scenario has appeared, with many novel rapidly growing species being described that are often responsible for disease in humans (Brown-Elliott & Wallace, 2002). The majority of such novel mycobacteria are not pigmented and have emerged from the splitting of the heterogeneous group known, until a few years ago, as the M. fortuitum complex (Wallace et al, 2004;Adékambi et al, 2006). Here, four strains of a scotochromogenic rapidly growing mycobacterium are described.…”
mentioning
confidence: 99%
“…It is a gram-positive, acid fast, pleomorphic bacillus, negative for pigmentation. 15 Mycobacteria are uncommon causes of peritonitis accounting for 3% of cases. Recent reports, however, suggest that the incidence of NTM peritonitis in patients on CAPD is on the rise.…”
Section: Discussionmentioning
confidence: 99%
“…al. 15 in their review identified 45 clinical isolates of M. porcinum. The most common site of isolation was wound infections (62%), followed by respiratory (18%), central intravenous catheter related infections (16%) and lymph nodes (2%).…”
Section: Discussionmentioning
confidence: 99%